A preliminary comparison of the Aravind aurolab drainage implant with the Baerveldt glaucoma implant: A matched case-control study. Issue 2 (March 2021) - Hafeezullah, Najla; AlHilali, Sara; Alghulaydhawi, Fahad; Edward, Deepak P; Ahmad, Sameer; Malik, Rizwan
Purpose: The Aurolab ® aqueous drainage implant is a low-cost alternative to the Baerveldt glaucoma implant. The aim of this study was to test the hypothesis that the two implants are comparable in terms of surgical success and safety. Methods: We conducted a retrospective case-control study of Aurolab aqueous drainage implant done at our institution from May 2015 and May 2017. Twenty-five consecutive patients who received an Aurolab aqueous drainage implant were matched by age and diagnosis to patients who received a Baerveldt glaucoma implant. Data were collected pre-operative and post-operative visits, including visual acuity and intraocular pressure, number of medications, and complications. Surgical success was defined as intraocular pressure between 5 and 21 mmHg with a minimum 20% reduction from baseline, without loss of light perception or the need for further glaucoma surgery. Cox regression analysis was used to predict factors associated with surgical success. Results: The median (interquartile range, IQR) intraocular pressure at 1 year was 16.0 (8.0) mmHg for the Baerveldt glaucoma implant and 13.0 (8.0) mmHg for the Aurolab aqueous drainage implant, p = 0.38. Success (mean ± SE) at 1 year for the intraocular pressure >21-mmHg failure criterion was 65% ± 15% for the Baerveldt glaucoma implant and 79% ± 11% for the Aurolab aqueous drainage implant (p = 0.80). The frequency of complications listed was similar for the two groups (Fisher's exact p = 0.71). In the Cox regression, the type of implant was not found to be associated with surgical success. Conclusions: Our preliminary results suggest that the Aurolab aqueous drainage implant is comparable to the Baerveldt glaucoma implant. Further long-term data in a larger population are needed to confirm these findings.